Pengaruh Pengeluaran Pemerintah Sektor Pendidikan, Kesehatan dan Infrastruktur terhadap Pertumbuhan Ekonomi dan Indeks Pembangunan Manusia - Asnidar Asnidar; Adelia Putri; Nurlaila Hanum (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of government spending in the education, health and infrastructure sectors on economic growth and HDI in Aceh Tamiang Regency. The data used are time series data for the period 2014-2023. The data analysis method uses path analysis. The results of the study indicate that government spending in the education, health and infrastructure sectors directly has a positive and insignificant effect on economic growth in Aceh Tamiang Regency. Directly, government spending in the education sector has a negative and insignificant effect on HDI in Aceh Tamiang Regency. Meanwhile, government spending in the health sector, infrastructure sector and economic growth directly have a positive and significant effect on HDI in Aceh Tamiang Regency. Indirectly, government spending in the education sector through economic growth has a negative and insignificant effect on HDI in Aceh Tamiang Regency. Meanwhile, government spending in the health sector, infrastructure sector through economic growth indirectly has a positive and significant effect on HDI in Aceh Tamiang Regency. The coefficient of determination value of 0.9998 indicates that 99.98% of the information contained in the data can be explained by the model, while the remaining 0.02% is explained by other variables outside the model, such as poverty, unemployment, population and other variables.